2016
DOI: 10.5216/sig.v28i2.41228
|View full text |Cite
|
Sign up to set email alerts
|

Exclamatives and interrogatives with ‘ques’: the CP/DP hierarchy and the plural marking in Brazilian Portuguese

Abstract: This paper examines exclamatives and interrogatives containing the whdeterminer 'ques' in dialectal Brazilian Portuguese. As opposed to standard BP, in these structures, 'que' is the only constituent of the DP marked for plural. In order to explain these facts, I will propose an analysis that accounts for the CP/DP-internal hierarchy as well as the DP-internal distribution of the plural morpheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
0
0
2
Order By: Relevance
“…In doing so, this paper continues a broader research (PEREIRA, 2016a(PEREIRA, , 2016b(PEREIRA, and 2017 that has already concluded analyses of other structures of BP with apparent "inconsistencies" in nominal agreement. Among the results, it was found that there is no inconsistency, but a coherent and universal pattern that governs agreement, as we will see in the section 2 of this paper.…”
Section: Introductionsupporting
confidence: 53%
“…In doing so, this paper continues a broader research (PEREIRA, 2016a(PEREIRA, , 2016b(PEREIRA, and 2017 that has already concluded analyses of other structures of BP with apparent "inconsistencies" in nominal agreement. Among the results, it was found that there is no inconsistency, but a coherent and universal pattern that governs agreement, as we will see in the section 2 of this paper.…”
Section: Introductionsupporting
confidence: 53%
“…Com base em Danon (2011) e Norris (2014), Pereira (2017) demonstrou que NumP funciona, no PB não padrão, como uma fronteira sintática na qual sintagmas à esquerda de cardinais são marcados com o morfema de plural, enquanto sintagmas à direita são não marcados. Essa regra pode ser observada em (1), exemplos de concordância em PB não padrão, e em (2), estruturas recorrentes no dialeto mineiro (NUNES, 2007, PEREIRA, 2016a).…”
Section: Estudos Sintáticos De Pb Dialetalunclassified
“…Sendo assim, neste trabalho, investiga-se de que modo a descrição formal de variedades do PB, especialmente do dialeto mineiro (VITRAL;RAMOS, 2006, RAMOS;PEREIRA, 2016aPEREIRA, , 2016bPEREIRA, , 2017PEREIRA, , 2018aPEREIRA, , 2018b, pode contribuir para a execução dessa proposta. Trata-se, portanto, de um trabalho que contém três etapas.…”
Section: Introductionunclassified